2014
DOI: 10.2108/zsj.31.180
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Morphological Discrimination Between an Invasive Ascidian,Ascidiella aspersa, and Its CongenerA. scabra(Urochordata: Ascidiacea)

Abstract: The solitary ascidian Ascidiella aspersa (Müller, 1776) has sometimes been regarded as conspecific with A. scabra (Müller, 1776), although previous detailed morphological comparisons have indicated that the two are distinguishable by internal structures. Resolution of this taxonomic issue is important because A. aspersa has been known as a notoriously invasive ascidian, doing much damage to aquaculture e.g. in Hokkaido, Japan. We collected many specimens from European waters (including the Swedish coast, near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…Using molecular data, Nishikawa et al (2014) confirmed the morphological differentiation (distinguishable morphologically by comparing the number of branchial tentacles with that of inner longitudinal vessels on each side) of Ascidiella aspersa from A. scabra (Müller, 1776), which had been previously doubted by some taxonomists. Therefore, the specific identification and differentiation of species of the genus is now possible, even for formalin-preserved immature specimens.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Using molecular data, Nishikawa et al (2014) confirmed the morphological differentiation (distinguishable morphologically by comparing the number of branchial tentacles with that of inner longitudinal vessels on each side) of Ascidiella aspersa from A. scabra (Müller, 1776), which had been previously doubted by some taxonomists. Therefore, the specific identification and differentiation of species of the genus is now possible, even for formalin-preserved immature specimens.…”
Section: Introductionmentioning
confidence: 54%
“…The specimens of Ascidiella aspersa living on the ropes at Nishikawa et al (2014) suggested that the previous records of "Ascidiella aspersa", including alien populations, might sometimes be unreliable, because of the lack of morphological or molecular information to distinguish A. aspersa from A. scabra, both of which are known as colonizers (for the latter species see Nishikawa and Otani, 2004). In the Pacific Ocean, Brewin's (1946) description of A. aspersa in New Zealand is informative, from which its introduction to the southern half of the Pacific Ocean about 1945 seems definitely to be the earliest.…”
Section: Ecological Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ascidiella aspersa eggs and early embryos are also transparent and also translate well microinjected mRNAs encoding proteins coupled to GFPs and could be used for this type of project when Phallusia is not available (Levasseur & McDougall, 2000). Ascidiella has a more widespread distribution than P. mammillata, e.g., it can be collected at Woods Hole, USA as well as in Europe, and northern Japan (Nishikawa et al, 2014) although its gametes are not as abundant as those of Phallusia.…”
Section: Preparing Ascidian Eggs and Spermmentioning
confidence: 99%
“…A. senegalensis Michaelsen, 19143 Nishikawa & Otani 2004Nishikawa et al 2014 A. scabra Berrill 1928;Lindsay & Thompson 1930;Berrill 1950A. senegalensis Michaelsen 1915 2012 2013 2010 3 2013 8 20 Fig.…”
mentioning
confidence: 99%